Problems of Identification of Material Parameters for Different Types of Viscoplastic Constitutive Equations - Kłosowski, P.; Woźnica, K. (Engineering Transactions, 1999)
In the paper the problem of identification of the material parameters of the elasto-viscoplastic constitutive equations is considered. A method based on the uniaxial tension tests for the Bodner -Partom law and two methods (from the tension and cyclic tests) for the Chaboche laws are presented. The parameters for both models for mild steel are directly calculated from the tension tests. Additionally, the numerical simulation of the cyclic loading tests is used for identification of the Chaboche model parameters. Results of the identification are verified in the viscoplastic analysis of vibrations of circular plates.